Myth-manipulation through Dismemberment in Michael Ondaatje's the man with seven toes - Lewis, Tanya (Studies in Canadian Literature / Études en littérature canadienne)

(untitled) (The University of New Brunswick, 1999)
In the man with seven toes, Michael Ondaatje takes the bare fragments of a myth sustained on gossip and only marginal to orthodox "history" to create a raw landscape of bodies blurred between unity and disunity, strung strenuously across the gap between what Dennis Lee refers to as "earth" and "world." Ondaatje juxtaposes unlike images and ideas and fragments language, forcing both his characters and his readers to immerse themselves in a disjointed world that defies simple categorization. Neither the myth nor the manner in which Ondaatje manipulates that myth allows for reader complacency.